2010
DOI: 10.1161/strokeaha.110.599159
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Hospital Readmission After Stroke

Abstract: Background and Purpose-Risk-standardized hospital readmission rates are used as publicly reported measures reflecting quality of care. Valid risk-standardized models adjust for differences in patient-level factors across hospitals. We conducted a systematic review of peer-reviewed literature to identify models that compare hospital-level poststroke readmission rates, evaluate patient-level risk scores predicting readmission, or describe patient and process-of-care predictors of readmission after stroke. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
131
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(137 citation statements)
references
References 20 publications
4
131
2
Order By: Relevance
“…Previously reported estimates for 30-day readmission rates in patients with stroke have varied from 6.5% to 24.3%, depending on the study methods used to ascertain readmissions. 9 Another recent study reported risk-standardized readmission rates for patients with ischemic stroke, ranging from 9.2% to 19.2% for hospitals with Joint Commission-certified primary stroke centers and 8.8% to 18.4% for hospitals without primary stroke Elective procedures should be coordinated during the index hospitalization or beyond 30 days of discharge. Outpatient clinic appointments should be scheduled prior to discharging the patient, especially among patients who have no primary care physician; consider scheduling outpatient follow-up appointments within 10 days of discharge.…”
Section: Discussionmentioning
confidence: 99%
“…Previously reported estimates for 30-day readmission rates in patients with stroke have varied from 6.5% to 24.3%, depending on the study methods used to ascertain readmissions. 9 Another recent study reported risk-standardized readmission rates for patients with ischemic stroke, ranging from 9.2% to 19.2% for hospitals with Joint Commission-certified primary stroke centers and 8.8% to 18.4% for hospitals without primary stroke Elective procedures should be coordinated during the index hospitalization or beyond 30 days of discharge. Outpatient clinic appointments should be scheduled prior to discharging the patient, especially among patients who have no primary care physician; consider scheduling outpatient follow-up appointments within 10 days of discharge.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Readmissions within 1 month of discharge may reflect unresolved problems at discharge, 5 the quality of immediate posthospital care, a more chronically ill population, or because of a combination of these factors. 6 A study in the United States provided evidence that patients with acute stroke who were readmitted within 30 days had a worse chance of survival and incurred greater healthcare costs than patients who were not readmitted. 7 Preventing avoidable readmissions may reduce costs to the healthcare system.…”
mentioning
confidence: 99%
“…[10][11][12][13] In 2008, the Centers for Medicare & Medicaid Services (CMS) began publicly reporting hospitallevel risk-standardized 30-day mortality and readmission rates for these conditions. [14][15][16][17][18] Although similar measures are not currently available for stroke, 19 such measures are planned. High risk-standardized mortality rates (RSMRs) and risk-standardized readmission rates (RSRRs) may indicate poorer quality of care, unresolved problems at initial discharge, the quality of immediate posthospital care, a more chronically ill population, or combinations of these factors.…”
mentioning
confidence: 99%